Economics beyond the millennium - Kirman, A. P.; q; Oxford eBooks; Association of Southern European Economic Theorists (Oxford : Oxford University Press, 1999)
This work contains articles by leading authorities in various fields of economic theory and econometrics, each of whom gives an account of the current state of the art in their own field and indicates the direction that they think it will take.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Economic forecasting; Econometric models; Twenty-first century -- Forecasts; Electronic books